Removal of Infected Muslim Body Covid-1 According to MUI Fatwa No. 18 Years 2020 - Fakhrurazi, Fakhrurazi; Marshinta, Adlia; Aulia, Hasanah; Gula, Rajiv Nazry Faizullah Sina; Setiawan, Wawan; Rosfiani, Okta (Journal of Progressive Law and Legal Studies, 2024)
As a result of the COVID-19 pandemic, infected individuals have spread far and fatally affected a significant number of people. Indonesia is fearful and nervous about getting COVID-19. Even when COVID-19 patients have passed away, the virus can still spread to others who come into contact with a dead body. The qualitative, statutory, and normative research approach used to write this thesis is library research (library research) based on secondary sources. A qualitative investigation was carried out on the numerous documentary studies that have been done, which were done by looking through and perusing a variety of literature. Qualitative data is descriptive in nature, meaning it is gathered using words rather than statistics. The study's findings indicate that managing Muslim bodies infected with Covid-19 differs from handling corpses in general and calls for specific handling in accordance with MUI fatwa no. 18 of 2020 for managing the bodies of Muslims infected with Covid-19, in order to prevent infection of the general public and law enforcement personnel performing their duties.